The impact of the rural digital economy on China’s new-type urbanization - Nan Chen (PLoS ONE, 2025)
The Chinese government is vigorously implementing the rural revitalization strategy and accelerating the process of new-type urbanization. The rapid development of the rural digital economy has emerged as a new driving force for new-type urbanization. This study aims to explore how the rural digital economy impacts China’s new-type urbanization from direct, heterogeneous, and indirect perspectives. Using the provincial-level panel data in China from 2014 to 2022, a mixed-methods approach is employed for the empirical research. The CRITIC and Entropy TOPSIS are used to assess the comprehensive development level and temporal characteristics of the rural digital economy and new-type urbanization. Moreover, a global-local auto-correlation analysis is carried out to depict the spatial distribution of the two variables. Subsequently, a two-way fixed effects model is constructed to verify the direct impact of the rural digital economy on new-type urbanization, as well as its structural and spatial heterogeneity characteristics. Finally, an mediating effect model is established to explore the impact paths through which the rural digital economy impacts new-type urbanization. The results show that the rural digital economy has significantly promoted new-type urbanization. Specifically, rural digital infrastructure, digital transformation of agriculture, agricultural production service informatization have a significant positive effect, while the role of rural life digitization is not significant. The rural digital economy has more significant positive impact on population agglomeration and economic growth, followed by social public service, but has no significant impact on ecological environmental protection and urban-rural coordination. Additionally, the qualitative analysis identifies geographical region, poverty, demographic structure and social equality as notable influencing factors in this impact. Further mechanism analysis result indicates that the rural digital economy impacts new-type urbanization through rural human capital improvement, agricultural economic growth and rural industrial structure upgrading. This research contributes to the existing body of knowledge by providing the practical path of rural development to promote new-type urbanization in the context of the digital economy, also clarifies the weak points and key links in this process. It also highlights the need for further research into the institutional factors that influence this relationship to enhances the policy applicability.